2015
DOI: 10.5005/jp-journals-10024-1733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Thickness and Density in the Lower Incisors’ Region in Adults with Different Types of Skeletal Malocclusion using Cone-beam Computed Tomography

Abstract: Objectives: To evaluate the bone thickness and density in the lower incisors' region in orthodontically untreated adults, and to examine any possible relationship between thickness and density in different skeletal patterns using cone-beam computed tomography (CBCT). Materials and methods:The CBCT records of 48 patients were obtained from the archive of orthodontic department comprising three groups of malocclusion (class I, II and III) with 16 patients in each group. Using OnDemand 3D ® software, sagittal sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Unlike Al Masri' s study[20], our study found that the apical ABA, total ABA of the mandibular alveolar bone in the area of the lower anterior teeth were significantly thinner in patients of skeletal Class III group than that of skeletal Class II group on both of the labial and lingual sides (P<0.05). The ABA at 6 mm below the CEJ level on the lingual side was significantly thinner in patients in skeletal Class III than it was in patients in skeletal Class II (P<0.05).…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike Al Masri' s study[20], our study found that the apical ABA, total ABA of the mandibular alveolar bone in the area of the lower anterior teeth were significantly thinner in patients of skeletal Class III group than that of skeletal Class II group on both of the labial and lingual sides (P<0.05). The ABA at 6 mm below the CEJ level on the lingual side was significantly thinner in patients in skeletal Class III than it was in patients in skeletal Class II (P<0.05).…”
Section: Discussioncontrasting
confidence: 99%
“…The minimum sample size was calculated to be 19 patients in each group according to a previous study by Al-Masri et al [ 25 ] assuming the standard deviation of apical buccal thickness to be 1.42, d = 1.7, alpha = 0.05, and study power of 90%.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed some differences between the two groups such that the alveolar process thickness, the buccal cortical plate, and the interradicular space in the maxilla were greater in class III patients while the mandibular alveolar process was wider in class I patients [ 24 ]. Al-Masri et al [ 25 ] evaluated the thickness and density of bone in patients with different sagittal skeletal patterns and found greater alveolar bone thickness at the apical region of the buccal plate in class I and II patients compared with class III individuals. Also, the alveolar bone thickness at the cervical region of buccal cortical plate was greater in class I than class II patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies demonstrated a relationship between vertical facial types and alveolar bone support at different tooth levels. Several studies concluded that long-face patients frequently showed thinner anterior alveolar bone at the root apex compared with normal-face and short-face patients 4 , 9 - 11 Furthermore, a thin anterior alveolus was typical in normal-face Class III patients due to the dentoalveolar compensatory mechanism, 4 , 10 , 12 and in patients with severe bimaxillary protrusion. 4 Although thin apical alveolar bone was more frequently found in long lower facial height patients, it could be encountered in any other skeletal types.…”
Section: Introductionmentioning
confidence: 99%